JARINGAN SYARAF TIRUAN PREDIKSI JUMLAH PENGIRIMAN BARANG MENGGUNAKAN METODE BACKPROPAGATION ( STUDIKASUS: KANTOR POS BINJAI ) - Rahmadani, Feri; Pardede, Akim M.H.; Nurhayati, Nurhayati (JTIK (Jurnal Teknik Informatika Kaputama), 2021)
Artificial neural networks are a branch of AI (Artificial Intelligence). Artificial neural network is an information processing paradigm which is inspired by the human brain system in receiving information and solving problems by carrying out the learning process through changes in the weight of its synapses. Pos Indonesia is an Indonesian state-owned company engaged in postal services. Currently, the form of Pos Indonesia business entity is a Limited Liability Company and is often referred to as PT. Indonesian post. This research was conducted to obtain a time benchmark when the delivery process occurs so that it can be used as a reference in shipping management control. The number of shipments of goods can be predicted by one method for prediction, namely the Backpropagation method. The Backpropagation method is a learning algorithm to reduce the error rate by adjusting the weight based on the difference in output and the desired target. This study uses unemployment data from the previous 3 years as training test data and training target data. After conducting the discussion, it produces an error value of 0.020043915 in iteration I. The results cannot be used because the error rate has not reached the target, which is 0.01.